Antimicrobial as growth promoters (AGP) in poultry balanced feed: use, bacterial resistance, new alternatives and replacement options (Veterinary Science, 2018)
By the end of the 40s´ in the last century, antibiotics were usedin animals´ diets, with the aim to increase meat, eggs and milkproduction. The results from the productive point of view werehighly positive. However, overtime, this practice was questionedfrom the public health point of view due to its implications in thegeneration of resistance to the antimicrobial used in treatments.Thus, in 2003, the European Union started with the instructionsof the prohibition of its use. With respect to poultry production,the non-therapeutic use of antimicrobial is questioned not onlyfor diseases prevention (profilaxis) but for the growth stimulationas well, what means to administer sub-therapeutic doses toanimals generally through feed with the purpose of increasingtheir productivity and growth rate. The current challenge is tofind compounds which achieve the same beneficial results in theproduction as the antimicrobial in growth promotion withoutadverse effects for such use
Keywords: antimicrobial; growth promoters; bacterial resistance; AGP.